Porous membrane as well as preparation method and application thereof
By using ultraviolet laser hole drilling technology, a porous membrane with high mechanical strength and small pore size was prepared, which solved the safety hazards and energy density of the electrolyte membrane in lithium-ion batteries and improved the safety and rate performance of the battery.
Patent Information
- Application Number
- CN202411246119.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The liquid organic electrolytes of existing lithium-ion batteries have the characteristics of flammability, leakage, and volatileness, which lead to safety hazards. In addition, traditional solid electrolyte membrane drilling methods are difficult to adjust the pore size and distribution, resulting in short circuits of the battery and reduced energy density.
Ultraviolet laser light source with short wavelength, high absorption rate of the film material and low thermal effect are used to laser holes on the base film to form a porous film with small average pore size, high surface flatness and high mechanical strength.
The high mechanical strength and small aperture of the battery separator are achieved, which avoids battery short circuits and energy density reduction, and improves the battery's safety performance and rate performance.
Smart Images

Figure CN119115268A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and relates to a porous membrane and a preparation method and application thereof. Background Art
[0002] Commercial lithium-ion batteries currently mainly use organic liquid electrolytes. However, due to the characteristics of organic solvents being flammable, easy to leak, and easy to volatilize, there are potential risks such as battery overcharging and short circuits, which make liquid organic electrolyte lithium-ion batteries have certain safety hazards in use. All-solid-state lithium batteries are expected to solve safety problems such as electrolyte leakage, combustion, and short circuits caused by lithium dendrites piercing the diaphragm in liquid lithium batteries.
[0003] The current mainstream solid electrolyte membrane is usually obtained by punching holes in the film. Conventional punching methods include laser drilling, mechanical drilling, chemical etching, particle beam bombardment, etc. Among them, the hole spacing and pore size created by mechanical drilling are too large, and it is difficult to adjust the pore size and spacing. Chemical etching not only requires a large amount of etching solution, but also often requires other punching methods to form a porous structure after etching is completed, and the membrane production efficiency is low. Particle beam bombardment has a high efficiency, but it requires an additional accelerator, resulting in high drilling costs, and the holes formed by particle beam bombardment have a strong random distribution, making it difficult to control the hole distribution.
[0004] Laser drilling is to use a high-power density laser beam to irradiate the processed material, so that the material is quickly heated to the vaporization temperature and evaporated to form holes. In the prior art, the material is punched with an infrared laser light source. However, the minimum aperture that can be obtained by infrared laser processing is limited by the wavelength and lens diffraction effect, and it is difficult to be less than 400nm. The aperture of the prepared laser-punched membrane is large, which is easy to cause battery short circuit when used in the diaphragm. In addition, the thermal effect generated by the infrared laser is strong. The molten polymer produced during the punching process will accumulate on the surface around the hole, forming a significant crater shape, making the surface of the porous membrane uneven, significantly increasing the thickness of the membrane, and reducing the volume energy density of the battery when used in the battery diaphragm. The uneven surface causes uneven internal stress distribution on the surface of the porous membrane, which reduces the mechanical strength of the porous membrane and makes it difficult to apply to the coating and assembly process of the battery. Summary of the invention
[0005] The present invention provides a method for preparing a porous membrane. The porous membrane formed by punching with an ultraviolet laser light source with a shorter wavelength, higher membrane material absorptivity and lower thermal effect has the advantages of small average pore size, high surface flatness and high mechanical strength.
[0006] The present invention also provides a porous membrane. Since the porous membrane is prepared by the above-mentioned preparation method, it has the advantages of small average pore diameter, high surface flatness and high mechanical strength.
[0007] The present invention also provides a diaphragm, including the above-mentioned porous membrane. The diaphragm is used in a battery to avoid the reduction of energy density caused by the increase of battery thickness, and its smaller pore size can avoid battery short circuit caused by contact between positive and negative electrodes, and its higher mechanical strength can enhance the puncture resistance of the diaphragm.
[0008] The present invention also provides a battery having excellent energy density, safety performance and rate performance.
[0009] The first aspect of the present invention provides a method for preparing a porous membrane, comprising: using a laser light source in the ultraviolet light band to perform laser drilling treatment on a base membrane to obtain the porous membrane.
[0010] In the preparation method as described above, the laser light source in the ultraviolet light band is selected from one or more of a rare gas excimer laser, a rare gas halide excimer laser, and a halogen gas excimer laser.
[0011] In the preparation method as described above, the thickness of the porous membrane is 0.5 to 20 μm.
[0012] In the preparation method as described above, the power of a single light source for the laser drilling process is 0.5W to 20W.
[0013] In the preparation method as described above, the material of the base film is selected from one or more of polyethylene terephthalate, polyimide, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyphenylene sulfide, and polybenzimidazole.
[0014] A second aspect of the present invention provides a porous membrane prepared by the preparation method described above.
[0015] The porous membrane as described above, wherein the pore size of the porous membrane is less than 500 nm.
[0016] A third aspect of the present invention provides an electrolyte membrane comprising the porous membrane as described above.
[0017] The electrolyte membrane as described above, wherein the electrolyte membrane comprises the porous membrane and a solid electrolyte filled in pores of the porous membrane.
[0018] A fourth aspect of the present invention provides a battery comprising the electrolyte membrane as described above.
[0019] The implementation of the present invention has at least the following advantages:
[0020] 1) The preparation method of the porous membrane provided by the present invention uses a laser light source in the ultraviolet band to punch holes to form the porous membrane. Compared with the traditional infrared laser punching, the ultraviolet laser has a lower thermal effect, which can avoid the protrusion of the crater-shaped melt deposits generated during the punching process, avoid the surface unevenness of the porous membrane and the uneven internal stress distribution on the surface, and at the same time, conventional membrane materials have a high absorption rate for ultraviolet light, and can achieve efficient and accurate punching even under a lower thermal effect. Therefore, the preparation method of the present invention has the advantage of high punching efficiency, and the porous membrane prepared by the method has a higher surface flatness, higher mechanical strength and a smaller average pore size.
[0021] 2) The porous membrane provided by the present invention is prepared by the above-mentioned preparation method, so the porous membrane has the advantages of small average pore size, high surface flatness and high mechanical strength. The porous membrane is used in the electrolyte membrane to avoid the problem of reduced battery energy density and reduced safety performance caused by surface unevenness.
[0022] 3) The battery provided by the present invention comprises the above-mentioned electrolyte membrane, so the battery has excellent energy density, safety performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a SEM image of the porous membrane of Example 1 of the present invention;
[0024] Figure 2 This is a SEM image of the porous membrane of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The aperture of the porous membrane formed by laser drilling is closely related to the wavelength of the laser. The traditional infrared laser drilling method has a limit focus spot size because the wavelength of infrared light is greater than 760nm and the laser beam is a Gaussian beam. The laser beam of a certain wavelength has a limit focus spot size. In theory, the focus spot size is proportional to the square of the laser divergence, the wavelength and the focal length of the lens, and inversely proportional to the diameter of the laser light outlet. The laser beam also has a diffraction limit, which makes it difficult to further focus the beam. Usually the diffraction limit is close to or slightly greater than the laser wavelength. Therefore, it is difficult to obtain a porous membrane with an aperture less than 400nm by infrared laser drilling. The conventional organic polymer materials used for diaphragms have too low absorption rates for visible light, making it difficult to drill holes with visible light laser light sources.
[0027] Based on this, the first aspect of the present invention provides a method for preparing a porous membrane, comprising: using a laser light source in the ultraviolet light band to perform laser drilling treatment on a base membrane to obtain a porous membrane.
[0028] The laser wavelength in the ultraviolet band is relatively short, within the range of 100nm to 400nm, so the preparation method of the present invention can produce a porous membrane with a pore size less than 200nm. In addition, conventional membrane materials, such as polyester, have chemical bonds that absorb ultraviolet light. When receiving ultraviolet light irradiation, the ultraviolet light can be used to break its chemical bonds without producing obvious thermal effects, thereby accurately punching holes in the base membrane. The lower thermal effect can avoid the formation of crater-shaped melt deposits on the upper and lower surfaces around the holes, thereby preparing a porous membrane with a smaller pore size, higher surface flatness and mechanical strength.
[0029] The base film in the present invention can be either a porous film with a certain pore structure or a non-porous film.
[0030] The present invention does not specifically limit the type of ultraviolet laser light source selected in the laser drilling process, which can be selected from conventional ultraviolet laser light sources, including but not limited to one or more of rare gas excimer lasers, rare gas halide excimer lasers, and halogen gas excimer lasers.
[0031] In a preferred embodiment, the laser light source in the ultraviolet band is selected from one or more of Xe2 excimer laser, Ar2 excimer laser, ArF excimer laser, KrF excimer laser, XeCl excimer laser and F2 excimer laser.
[0032] Among them, the wavelength of Xe2 excimer laser is 172nm, the wavelength of Ar2 excimer laser is 126.1nm, the wavelength of ArF excimer laser is 193nm, the wavelength of KrF excimer laser is 248nm, the wavelength of XeCl excimer laser is 308nm, and the wavelength of F2 excimer laser is 157nm. All of the above laser light sources have high drilling accuracy and low thermal effect, and the wavelength distribution is wide. You can choose from the above laser light sources according to the required aperture.
[0033] From the perspectives of photon energy, pore-forming efficiency and cost, it is more preferred to use ArF excimer laser or KrF excimer laser as the laser light source.
[0034] In a specific embodiment, the thickness of the porous membrane is 0.5 to 20 μm. Exemplarily, the thickness of the porous membrane can be 0.5 μm, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 20 μm or a range consisting of any two of the above values. The porous membrane with the above thickness range is applied to the battery to avoid the mechanical strength of the electrolyte membrane being affected by too small a thickness, and to avoid the volume energy density of the battery being affected by too large a thickness.
[0035] The present invention does not specifically limit the device for laser drilling processing, and the laser drilling processing can be performed by selecting a conventional laser drilling device in the art. For example, an array laser drilling device can be used for drilling.
[0036] The power of the light source is also an important factor affecting the quality of the prepared porous membrane. If the power is too high, it is easy to produce a strong thermal effect, resulting in the accumulation of melt on the surface of the porous membrane. If the power is too low, it is difficult to achieve the required processing efficiency. Based on the above considerations, the power of a single light source in the laser drilling process is preferably 0.5W to 20W. Among them, the power of a single light source refers to the power of a single excited state optical element in the process of dot matrix drilling or dense drilling. Exemplarily, the power of a single light source can be 0.5W, 1W, 3W, 5W, 8W, 10W, 13W, 15W, 18W, 20W or a range consisting of any two of these values.
[0037] In a preferred embodiment, the material of the base film is selected from one or more of polyethylene terephthalate (PET), polyimide (PI), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polyetheretherketone (PEEK), polyphenylene sulfide (PPS), and polybenzimidazole (PBI). The above polymers not only have a higher absorption rate for lasers in the ultraviolet band, which is conducive to achieving high-efficiency drilling, but also have excellent heat resistance. When used in the electrolyte membrane, the battery can have higher safety performance.
[0038] The second aspect of the present invention provides a porous membrane, which is prepared by the preparation method as described above. Since the porous membrane is obtained by laser drilling a non-porous membrane with an ultraviolet laser, wherein the ultraviolet laser has a shorter wavelength, a lower thermal effect, and the membrane material has a higher absorption rate to it, the porous membrane has the advantages of a small average pore size, a high surface flatness, and a high mechanical strength.
[0039] Furthermore, the pore size of the porous membrane is less than 500 nm. Exemplarily, the pore size of the porous membrane can be 480 nm, 450 nm, 400 nm, 350 nm, 300 nm, 250 nm, 200 nm, 150 nm, 100 nm, 50 nm or a range consisting of any two of the above values. The above porous membranes with small pores are applied to electrolyte membranes, which is beneficial to reduce the contact probability of positive and negative electrodes and improve the safety performance of batteries.
[0040] The third aspect of the present invention provides an electrolyte membrane, including the porous membrane as described above. Since the porous membrane has a smaller pore size, the electrolyte membrane can also have a smaller pore size, which reduces the contact probability of the positive and negative electrodes while ensuring the passage of ions, and avoids the occurrence of battery short circuit; in addition, the high surface flatness and mechanical strength of the porous membrane itself can also make the electrolyte membrane have higher safety performance during application, and can also avoid the increase of battery thickness and reduce the negative impact on battery energy density. Compared with the traditional porous membrane formed by punching with an infrared laser light source, the porous membrane formed by the present invention using an ultraviolet laser light source has a smaller pore size, and can achieve an average pore size of 1μm or less.
[0041] In a preferred embodiment, the electrolyte membrane includes a porous membrane and a solid electrolyte filled in the pores of the porous membrane. Compared with the traditional diaphragm with a solid electrolyte layer only coated on the surface of the base membrane, filling the solid electrolyte in the pores of the porous membrane can increase the channel tortuosity of the straight-through hole, thereby having a lower air permeability and better ion conduction characteristics, which is conducive to the transmission of lithium ions, can improve the rate performance of the battery, and reduce the directness of the pores, improve the insulation strength of the electrolyte membrane, and reduce the probability of battery short circuit.
[0042] The present invention does not specifically limit the type of the above-mentioned solid electrolyte, which can be selected from solid electrolytes conventionally used in the art, including but not limited to one or more of oxide solid electrolytes, polymer solid electrolytes, sulfide solid electrolytes, and gel electrolytes. Among them, the oxide solid electrolyte is preferably aluminum titanium phosphate (LATP) or lithium lanthanum zirconium oxide (LLZO), the polymer solid electrolyte is preferably copolymer-modified polyethylene oxide (PEO), and the sulfide solid electrolyte is preferably Li6PS5Cl.
[0043] In a specific embodiment, the electrolyte membrane comprising a porous membrane and a solid electrolyte filled in the pores of the porous membrane can be prepared by the following method:
[0044] The solid electrolyte is made into slurry and then coated on the porous membrane, and then dried and solidified to obtain the electrolyte membrane.
[0045] The coating method can be selected from one or more of screen roller coating, wire rod coating, dip coating and extrusion coating; the drying temperature is preferably 60-80°C.
[0046] The fourth aspect of the present invention provides a battery, comprising the electrolyte membrane provided by the third aspect of the present invention. Since the electrolyte membrane has good surface flatness, high mechanical strength and higher insulation strength, the battery has good safety performance while maintaining a high energy density.
[0047] The battery of the present invention may be a liquid battery, a solid-state battery, or a semi-solid-state battery, and more preferably a solid-state battery or a semi-solid-state battery. In addition to the above-mentioned separator, the battery of the present invention further comprises a positive electrode sheet, a negative electrode sheet, and an electrolyte, wherein the positive electrode sheet, the negative electrode sheet, and the electrolyte may all refer to the positive electrode sheet, the negative electrode sheet, and the electrolyte conventionally used in lithium-ion batteries, and will not be described in detail here.
[0048] The porous membrane provided by the present invention and its preparation method and application will be further described in detail below through specific examples. Obviously, the following examples are only some embodiments of the present invention, not all embodiments. Based on the technical solutions and given embodiments provided by the present application, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention.
[0049] Example 1
[0050] This embodiment provides a porous membrane, a solid electrolyte membrane and a lithium ion battery, and the specific preparation method is as follows:
[0051] 1. Preparation of porous membrane
[0052] An array laser drilling device is used to perform laser drilling on a PET film with a thickness of 10 μm to obtain a porous film; wherein the light source for the laser drilling is selected from ArF excimer laser, the laser wavelength is 193 nm, and the single light source power is 5W.
[0053] 2. Preparation of solid electrolyte membrane
[0054] 1) adding 50 parts by weight of solid electrolyte powder LATP, 0.5 parts by weight of thickener CMC, 0.25 parts by weight of dispersant BYK-156, 5 parts by weight of adhesive GR401, 0.1 parts by weight of wetting agent BYK-348, and 50 parts by weight of deionized water into a double planetary slurry kettle, stirring at 2000 rpm / min for 120 min to obtain a coating slurry;
[0055] 2) The above-mentioned coating slurry is coated on the porous membrane prepared in step 1 by a dip coating process, and dried at a temperature of 60° C. to 80° C. to obtain a solid electrolyte membrane.
[0056] 3. Preparation and assembly of batteries
[0057] 1) The positive electrode active material NCM811, the conductive agent SP, the conductive agent KS-6, and the binder PVDF were added to the solvent NMP in a mass ratio of 90:2:1:3, mixed evenly to form a positive electrode slurry, and coated on a 10 μm aluminum foil current collector; then dried in an oven at 95° C., and rolled on a roller press for use.
[0058] 2) Add active material artificial graphite, conductive agent acetylene black and binder CMC / SBR (mass ratio 1:1) into water at a mass ratio of 90:5:5 and disperse evenly to prepare negative electrode slurry, which is then coated on a copper foil current collector with a thickness of 10 μm, dried in an oven at 85° C., and rolled on a roller press for later use.
[0059] 3) In a drying room with a dew point of <-40°C, place the solid electrolyte membrane between the positive electrode sheet and the negative electrode sheet for stacking and packaging, and heat it at 2.5g / m 2 The electrolyte (Xinzhoubang, LBC3008A) was injected in a proportion of to obtain a battery.
[0060] The porous membrane prepared in this example was subjected to SEM testing. Figure 1 is the SEM picture of the porous membrane of Example 1, as shown Figure 1 As shown, the surface of the porous membrane has almost no protrusions and has a high flatness.
[0061] Embodiments 2 to 8
[0062] Examples 2 to 8 provide a porous membrane, a solid electrolyte membrane and a lithium ion battery, respectively, wherein the preparation conditions of the porous membrane are different from those of Example 1, and the preparation conditions of the solid electrolyte membrane and the lithium ion battery are consistent with those of Example 1. The differences between the preparation conditions of the porous membrane and Example 1 are listed in Table 1, and for ease of comparison, the conditions corresponding to Example 1 are also listed in Table 1.
[0063] Table 1
[0064] Base film material Base film thickness / μm Laser light source type Single light source power / W Laser wavelength Example 1 PET 10 ArF excimer laser 5 193 Example 2 PET 10 KrF excimer laser 5 248 Example 3 PI 10 ArF excimer laser 5 193 Example 4 PET 10 ArF excimer laser 3 193 Example 5 PET 10 ArF excimer laser 7 193 Example 6 PET 20 ArF excimer laser 5 193 Example 7 PET 2 ArF excimer laser 5 193
[0065] Comparative Example 1
[0066] This comparative example provides a porous membrane, a solid electrolyte membrane and a lithium ion battery, and the specific preparation method is as follows:
[0067] 1. Preparation of porous membrane
[0068] An array laser drilling device is used to perform laser drilling on a PET film with a thickness of 10 μm to obtain a porous film; wherein the laser drilling light source is selected from a CO2 laser, the laser wavelength is 10.6 μm, and the single light source power is 5W.
[0069] The preparation conditions of the solid electrolyte membrane and the lithium-ion battery refer to Example 1 and are not described in detail here.
[0070] The porous membrane prepared in this comparative example was subjected to SEM testing. Figure 2 The SEM image of the porous membrane of Comparative Example 1 is shown in Figure 2 As shown, the molten polymer accumulated on the surface of the porous membrane during the punching process forms a significant crater shape, resulting in a significant increase in the overall thickness of the solid electrolyte membrane after coating.
[0071] Test Case
[0072] 1. The following properties of the porous membranes of the above embodiments and comparative examples were tested:
[0073] 1. Average thermal shrinkage at 200℃
[0074] Test method: Referring to GB / T36363-2018, the porous membrane was placed in a 200°C environment, treated for 1 hour, and the thermal shrinkage in MD and TD directions was calculated. The average value of the thermal shrinkage in MD and TD directions was taken as the average thermal shrinkage at 200°C.
[0075] 2. MD tensile strength
[0076] Test method: refer to GB / T36363-2018.
[0077] 3. Puncture strength
[0078] Test method: refer to GB / T36363-2018.
[0079] 4. Porosity
[0080] Test method: refer to GB / T36363-2018.
[0081] 5. Average pore size
[0082] Test method: Use PMI instrument to measure and obtain average pore size data. The pore size is expressed in μm or nm.
[0083] 6. Membrane breaking temperature
[0084] Test method: The porous membrane is placed in a tensioned state (simulating the state inside a battery), and the temperature is gradually raised to the point where the membrane breaks. The temperature at which the membrane breaks is the membrane breaking temperature of the porous membrane.
[0085] 7. Surface roughness
[0086] Test method: Use Olympus LEXT OLS5100 laser confocal microscope to test. Fix the porous membrane on the sample stage, adjust the objective lens magnification to 10X and start 3D acquisition scanning. Then click on the Correct Tilt tab in the analysis software, and select the Height / Mixed mode to calculate the surface roughness S under no filtering conditions. a Value. a The value is calculated as follows:
[0087]
[0088] 2. The following performance tests were performed on the solid electrolyte membranes of the above embodiments and comparative examples:
[0089] 1. Insulation strength
[0090] Test method: Place the solid electrolyte membrane between two electrodes, apply voltage between the electrodes, increase the voltage until the solid electrolyte membrane is broken down, and take the voltage value when the solid electrolyte membrane is broken down, which is the insulation strength.
[0091] 3. The lithium-ion batteries prepared in the above embodiments and comparative examples were tested for the following properties:
[0092] 1. Energy density
[0093] Test method: Test the soft-pack battery in the voltage range of 3.0V to 4.5V. The discharge platform voltage can be determined by cyclic voltammetry at a rate of 0.5C. Then, discharge at a constant current of 1C in a fully charged state to measure the discharge capacity. The volume energy density is calculated by the following formula:
[0094]
[0095] The test results of all the above performances are shown in Table 2.
[0096] Table 2
[0097]
[0098] In Table 2, >300 indicates that the membrane is not broken at a temperature above 300°C.
[0099] The following conclusions can be drawn from Table 2:
[0100] 1) By comparing Examples 1 and 2 with Comparative Example 1, it can be seen that the longer the wavelength of the laser used, the stronger the thermal effect of the laser, and the larger the pore size of the porous membrane formed. Among them, the CO2 laser light source used in Comparative Example 1 is an infrared laser, which has the strongest thermal effect. The average pore size of the obtained porous membrane is 25 μm, which is a micron-level pore, and the surface roughness and thermal shrinkage of the porous membrane are significantly larger, the MD tensile strength and puncture strength are significantly lower, and the solid electrolyte membrane and the battery formed using the porous membrane have low volume energy density.
[0101] 2) By comparing Example 1 with Example 3, it can be seen that compared with PET, the film breaking temperature of PI material is higher, and the tensile strength and puncture strength of the porous film formed are lower, but its insulation strength is higher. Taking all factors into consideration, the base film of PET material is more suitable.
[0102] 3) By comparing Examples 1, 4, and 5, it can be seen that the higher the power of the single light source used in the punching process, the larger the aperture formed. Correspondingly, the porosity also increases with the increase of power, and has no obvious effect on other properties.
[0103] 4) By comparing Examples 1, 6, and 7, it can be seen that under the same laser drilling conditions, the greater the thickness of the base film, the smaller the pore size of the porous film formed, but a larger thickness will lead to an increase in surface roughness, thereby reducing the tensile strength of the porous film. However, a larger thickness is beneficial to an increase in the puncture strength of the porous film and a decrease in the thermal shrinkage rate, but it will also lead to a decrease in the volume energy density of the battery.
[0104] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a porous membrane, characterized in that: include: The base film is subjected to laser drilling treatment using a laser light source in the ultraviolet light band to obtain the porous film.
2. The preparation method according to claim 1, characterized in that: The laser light source in the ultraviolet light band is selected from one or more of a rare gas excimer laser, a rare gas halide excimer laser, and a halogen gas excimer laser.
3. The preparation method according to any one of claims 1 or 2, characterized in that The thickness of the porous membrane is 0.5 to 20 μm.
4. The preparation method according to any one of claims 1 to 3, characterized in that The power of a single light source for the laser drilling process is 0.5W to 20W.
5. The preparation method according to claim 1, characterized in that: The material of the base film is selected from one or more of polyethylene terephthalate, polyimide, polybutylene terephthalate, polyethylene naphthalate, polyetheretherketone, polyphenylene sulfide, and polybenzimidazole.
6. A porous membrane, characterized in that The preparation method is described in any one of claims 1 to 5.
7. The porous membrane according to claim 6, characterized in that The pore size of the porous membrane is less than 500 nm.
8. An electrolyte membrane, characterized in that: Comprising the porous membrane according to claim 6 or 7.
9. The electrolyte membrane according to claim 8, characterized in that The electrolyte membrane includes the porous membrane and a solid electrolyte filled in pores of the porous membrane.
10. A battery, characterized in that: Comprising the electrolyte membrane according to claim 8 or 9.
Citation Information
Cited By
Difunctional light-operated pore-forming ion exchange membrane as well as preparation method and application thereof
CN120040816A
